Lingo Learn application as students' learning tool to enrich vocabulary: Students’ perspectives - Ramadhan Solin; Maryati Salmiah (English Learning Innovation, 2025)
Lingo Learn is an English learning application that is free to use, easy to access. It offers an interactive language learning experience that can improve English skills and expand the vocabulary of its users. The main purpose of this study is to find out students' perceptions of the "Lingo Learn" application as a learning tool to enrich students' vocabulary mastery. This research used qualitative methods with phenomenological study. The subjects of this study were 11th-grade students at SMAS Budi Agung Medan. The number of participants was 29 people, 21 female students and 8 male students. The selection of participants was carried out using a purposive sampling approach. Data were collected from questionnaire data, interviews, and direct observations. The findings of this study showed that the Lingo Learn application can enhance students' vocabulary. The researcher found five student perspectives on Lingo Learn application: Lingo Learn as an adaptable learning tool, effectiveness, efficiency, affordability, and interactivity, so that overall, Lingo Learn application can be used as a learning tool to enrich students' vocabulary acquisition. This study implies that incorporating technology into language teaching can improve accessibility and learning outcomes for diverse students.